Prevalence and predictors of complementary and alternative medicine use among people with coronary heart disease or at risk for this in the sixth Tromsø study: a comparative analysis using protection motivation theory. - Kristoffersen, Agnete Egilsdatter; Sirois, Fuschia; Stub, Trine; Hansen, Anne Helen (BMC Complementary and Alternative Medicine, 2017)
Source at https://doi.org/10.1186/s12906-017-1817-x Background: Engagement in healthy lifestyle behaviors, such as healthy diet and regular physical activity, are known to reduce the risk of developing coronary heart disease (CHD). Complementary and alternative medicine (CAM) is known to be associated with having a healthy lifestyle. The primary aim of this study was to examine the prevalence and predictors of CAM use in CHD patients, and in those without CHD but at risk for developing CHD, using Protection Motivation Theory (PMT) as a guiding conceptual framework. Method: Questionnaire data were collected from 12,981 adult participants in the cross-sectional sixth Tromsø Study (2007 – 8). Eligible for analyses were 11,103 participants who reported whether they had used CAM or not. Of those, 830 participants reported to have or have had CHD ( CHD group ), 4830 reported to have parents, children or siblings with CHD ( no CHD but family risk ), while 5443 reported no CHD nor family risk of CHD . We first compared the patterns of CAM use in each group, and then examined the PMT predictors of CAM use. Health vulnerability from the threat appraisal process of PMT was assessed by self-rated health and expectations for future health. Response efficacy from the coping appraisal process of PMT was assessed as preventive health beliefs and health behavior frequency. Results: Use of CAM was most commonly seen in people with no CHD themselves, but family risk of developing CHD (35.8%), compared to people already diagnosed with CHD (30.2%) and people with no CHD nor family risk (32.1%). All four of the PMT factors; self-rated health, expectations fo r future health, preventive health beliefs, and the health behavior index – were predictors for CAM use in the no CHD but family risk group . Conclusion: These findings suggest that people use CAM in response to a perceived risk of developing CHD, and to prevent disease and to maintain health.